FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI KEWIRAUSAHAAN - B01112058, Fajar Afghani (Jurnal Pembangunan dan Pemerataan, 2017)
Abstract : The purpose of this study is to examine and analyze the factors that influence student motivation in entrepreneurship at the Faculty of Economy and Business class of 2013, Tanjungpura University. The independent variables are entrepreneurship education, personality, impetus excel, the family, and work experience, while the dependent variable is the motivation of entrepreneurship. The result of hypothesis in this study shows that entrepreneurship education has positive and significant influenced towards motivation of entrepreneurship. The personality has positive and not significant influenced towards motivation of entrepreneurship. The impetus excel has negative influenced towards motivation of entrepreneurship. The family has positive and not significant influenced towards motivation of entrepreneurship. Meanwhile, work experience has negative and not significant towards motivation of entrepreneurship.Keywords : motivation of entrepreneurship, entrepreneurship education, personality, impetus excel, family, work experience.